Soil Quality, Pollution Indices and Health Risk of Metals and PAHs at a Crude-Oil Spill Site in Okpohovor, Delta State, Nigeria - Peter Mamuro Eguvbe; Solomon Erhajemu Ogoron; Eze Wealth Odali; Ijeomah Faith Ogwu; Chinedu Jude Ossai; Anthony Anwuli Ogbuta; Chukwujindu Maxwell Azubuike Iwegbue; Godwin Ebichime Nwajei (Sriwijaya Journal of Environment, 2026)
Background: Oil spillage is a major driver of soil degradation in the Niger Delta, yet integrated, site-specific assessments coupling metals, polycyclic aromatic hydrocarbons (PAHs) and quantitative risk remain scarce. Objective: This study assessed the contamination status, source structure and ecological and human-health risk of soils at a crude-oil spill site in Okpohovor, Udu Local Government Area, Delta State, Nigeria. Methods: Soils from five points (S1–S5) and a control station were sampled at two depths (0–15 and 15–30 cm). pH, electrical conductivity, total organic carbon, particle size and nine metals were determined by flame atomic absorption spectrophotometry, and 16 priority PAHs by GC–MS. Pollution indices, principal component analysis (PCA), one-way ANOVA with effect sizes, and BaP-equivalent, hazard-index and incremental lifetime cancer-risk models were applied. Results: Soils were strongly acidic (pH 3.00–3.70) and sandy. All metals were below Department of Petroleum Resources (DPR) target values except cadmium (0.05–2.55 mg/kg), which reached the pollution range in 60% of samples. Clay differed significantly between sites (F=10.133, p=0.013, η²=0.890). PCA separated a lithogenic Pb–Cr–Ni–Fe association (PC1, 32.0%) from a cadmium-driven signal. The ecological risk index (9–263) was cadmium-dominated. ΣPAH reached 81,327 µg/kg from mixed petrogenic–pyrogenic sources; hazard indices were mostly below 1 but total cancer risk exceeded 1×10⁻⁶. Conclusion: Cadmium and carcinogenic PAHs are the priority contaminants, posing food-chain and public-health risks that warrant targeted remediation and sustained monitoring.